Assessment of the level of serum uric acid in patients of pre-eclampsia and their comparison with levels in normotensive pregnancy - Deshpande, Hemant G.; Madkar, Chandrakant S.; Shinde, Madhukar; Kothari, Vilisha S. (International Journal of Reproduction, Contraception, Obstetrics and Gynecology, 2018)
Background: Pre-eclampsia is one of the major causes of maternal and perinatal morbidity and mortality. There are various parameters to evaluate pre-eclampsia. S.uric acid levels is one of the important biochemical markers in pre-eclampsia. The objective of current study is to compare the levels of S.uric acid in pre-eclamptic patients and normotensive patients. Methods: A total of 256 antenatal patients, consisting of two groups, 128 patients in each group diagnosed with pre-eclampsia (either earlier or during examination) and 128 control antenatal patients in their third trimester were considered. Both the groups were compared in relation to age, parity, socio economic status and geographical variations. Blood sample (venous blood) of about 5ml was drawn from the ante cubital vein of the patient under all aseptic precautions to estimate S.uric acid levels. Results: The observation of present study shows that the level of serum uric acid is significantly higher in the cases of pre-eclampsia. The value of S.uric acid increases with the severity of pre-eclampsia. Conclusions: It is concluded from this study that high levels of uric acid are found in the serum of pre-eclamptic cases as compared to normotensive cases of the study population. The levels of uric acid are higher in severe cases as compared to the levels in mild and moderate cases.